Influence of Availability of Local Regional Food Preferences on Online Food Delivery Platform Choice and Consumer Loyalty - Tewari, Gaurav; Bisaria, Charu; Sharma, Vivek (International Review of Management and Marketing, 2026)
Online food Delivery platforms reflect consumers choices and preferences. The availability of local regional food not only leads to better consumer satisfaction but also paves the way for more food ordering culture. This paper focuses on investigating the availability of local regional food options of online food delivery platforms as Perceived Regional cuisine Adequacy (PCRA). The study also penetrates how availability of local and authentic dishes on OFD’s affect consumer ‘s choice for platform and loyalty. The angle of increased consumer satisfaction with increased availability of local cuisine food preferences was also tested. This strengthens the impact of PRCA on loyalty. Another important result is that a lack of regional cuisine options encourages multi-homing behaviour, where customers use multiple competing food delivery apps at the same time. The paper concludes that offering authentic regional cuisine is a valuable competitive strategy. Platforms that understand local food preferences can improve satisfaction, build loyalty, and reduce customer switching in a highly competitive market.